Estimation of aramid fiber/epoxy interfacial properties by fiber bundle tests and multiscale modeling considering the fiber skin/core structure. (1st May 2017) - Qi, Guocheng; Zhang, Boming; Du, Shanyi; Yu, Yalin
Abstract: In this work, the aramid fiber/epoxy interfacial normal bonding property and interfacial shear property were estimated by transverse fiber bundle tensile (TFBT) test and 45° fiber bundle tensile (45FBT) test, respectively. The fracture surfaces of the fiber bundle samples after the mechanical test were observed to investigate the micro failure mechanisms. The interfacial debonding was found coupled with fibrillation of the fiber surface due to the apparent skin/core structure of aramid fibers. Furthermore, the multiscale model based on the generalized methods of cells (GMC) considering the skin/core structure and the fiber/matrix interphase was established to calculate the micro stresses. The interfacial normal strength (IFNS) in the TFBT specimen and interfacial shear strength (IFSS) in the 45FBT specimen were determined by the combination of the experimental and analytical results. Eventually, the effects of skin/core stiffness and thickness on the calculated IFNS and IFSS values were investigated.